Thyroglossal duct cyst various clinical presentations and modified Sistrunk procedure: A single-center study in India - Ramesh babu G; Shamsheer Sk; Indraneel Reddy D (Golestan University Of Medical Sciences, 2022)
Background: Thyroglossal duct cysts (TGDCs) are the most common congenital cervical anomalies that account for about 2-4% of all midline neck swellings. They may present as a cyst, abscess, or sinus in the anterior neck region. The cysts are managed by the standard or a modified Sistrunk operation with the least chance of recurrence when compared to the removal of the cyst alone.  This study aimed to present our experience in the modified Sistrunk operation over thyroglossal duct cyst anomalies with particular emphasis on the clinical diversity in presentation, surgical technique, and management of postoperative complications. Methods: This prospective observational study was carried out on 25 newly diagnosed cases of TGDC, which were confirmed histologically and radiologically over a period of 5 years. Results: All patients underwent a modified Sistrunk operation under general anesthesia and followed up for 2 years. The surgery consisted of complete excision of the cyst with the removal of the central portion of hyoid bone and macroscopically evident duct tissue with intraoperative T-shaped closure of the muscular layer to restore the function of hyoid bone and reduce most postoperative complications, such as recurrence and swallowing difficulties. Conclusion: The results indicate that the modified Sistrunk operation is one of the best surgical procedures for the treatment of TGDC anomalies limited up to hyoid without lingual extension, especially to prevent a recurrence. More attention should be paid to supra and infra hyoid muscular closure to restore the normal function of the hyoid